Architecture vernaculaire de terre et évacuation des eaux - Blandine Besnard (Frontière·s)
Gradually abandoned since the 1970s, the vernacular heritage of the interior region of Oman is experiencing its last fires and there is an urgent need to collect both ethnological and architectural data before they definitely fall into the domain of History and Archaeology.With this in mind, a survey aiming to identify water drainage installations in three traditional mud-brick neighbourhoods in the interior of Oman (Birkat al‑Mawz, Izkī and al‑Ḥamrā') was carried out in March 2020.This survey highlighted the techniques and facilities related to water drainage in traditional Omani neighbourhoods that had never been the subject of any particular attention, but also opened up ethnoarchaeological perspectives, a discipline that postulates that ethnography can enrich the interpretation of archaeological data, or even the absence of the latter.Out of 359 identified installations, gargoyles represent 99% of the sample. The absence of ground installations (e.g. sump, drain, sewer) showed that very simple solutions for water management within a brick architecture made it possible to overcome the dichotomy of absence/failure or presence/performance pairs generated by the bias of archaeological data.